Property modification of chloroprene rubber by addition of ultra-fine acrylic rubber powder - P. Sae-Oui (2018)
© Institute of Materials, Minerals and Mining 2014. The role of ultra-fine pre-vulcanised acrylic rubber powder (ACMP) in properties of chloroprene rubber (CR) was studied. ACMP was incorporated into CR at various loadings and the properties of the ACMP filled CR were investigated. Owing to the high thermoplastic nature of the ACMP, better processability is obtained with increasing ACMP loading. Even though the presence of ACMP gives negative effect on cure rate and state of cure, both modulus and hardness of the vulcanisates increase continuously with increasing ACMP loading. The tensile strength is also improved with increasing ACMP loading up to 20 phr. Nevertheless, elasticity and abrasion resistance of the vulcanisates are impaired as the concentration of ACMP is increased. This is mainly attributed to the combination of dilution effect and reduced crosslink density. Since ACMP is fully saturated and highly polar, the incorporation of ACMP into CR gives rise to enhanced aging and oil resistance of the vulcanisates.